The Conflict Between Political Section and Military Section Through the Text of Al-Tabari Abu Muslim Al-Khorasani As A Model - Hussain Al-Shammari, Ashraq Ali; Al-Shammari, Abbas Ali Hussein (International Journal of Psychosocial Rehabilitation, 2020)
The current study deals with historian figure it is called: Al-Tabari historian is unique from others in dealing with historical texts, we find him in most of the narratives he conveys, he talks about the origin of the novel and transmits it in its entirety without leaving, unlike many other historians who came after it, so we find them quoting from it and leaving some words, the position of the political section and the military section in the Abbasid era I and II was of great importance over the course of history, so we find that two systems operate separately and separately from each other, The study was divided into an introduction, two studies, and a conclusion. In the first topic, we discussed the establishment of the state and the accession of Abu Al-Abbas Al-Saffah to the throne, and how his position was on his uncle Abdullah bin Ali, as well as the position of Abu Salamah Al-Khalal from standing next to the Abbasid state and how he managed to conceal the existence of the Abbasid family represented by Abu Al-Abbas Al-Saffah and the people of His house in Kufa, as for the second topic, we discussed the position of the opponent that Abu Muslim al-Khorasani adopted from the Abbasid state and how he managed to turn his hand toward the Khorasanians and the people close to him. Conclusion Gamma has had a large share to reach the most prominent points that we have achieved while we dealt with the research and stood up to the most prominent points that enriched the study.